Critical pseudo-double impulse analysis evaluating seismic energy input to reinforced concrete buildings with steel damper columns - Fujii, Kenji (Frontiers in Built Environment, 2024)
Steel damper columns (SDCs) are energy-dissipating members that are suitable for reinforced concrete (RC) buildings and are often used for multistory housing. The evaluation of the peak deformation and hysteretic dissipated energy of such building structures is essential for the rational seismic design of RC buildings with SDCs. In a previous study, the authors proposed an energy-based prediction procedure for the peak and cumulative response of an RC frame building with SDCs. In this procedure, the accuracy of the equivalent velocity of the maximum momentary input energy (VΔE1 * )-peak equivalent displacement (D1 * max) relationship is essential for high quality predictions. In this article, the VΔE1 * -D1 * max relationships of RC moment-resisting frames with and without SDCs are investigated using a critical pseudo-double impulse (PDI) analysis based on a study by Takewaki and coauthors. The results show that the VΔE1 * -D1 * max relationship obtained from the critical PDI analysis agrees well with that calculated from the equations proposed in the previous study. * 1